Atlanto-axial instability in psoriatic arthritis: a case report - Meiteen, Geoffrey P (1988)
Psoriatic arthritis involving the spine is uncommon. However, when it does, atlanto-axial instability may occur. Clinical and radiographic aspects of psoriatic arthritis are reviewed and illustrated with a case report.